PENGARUH PROFITABILITAS, MEKANISME GOOD CORPORATE GOVERNANCE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Yopeace, Yunita; Pratiwi, Devica; Ramli, Yosua (APPS Publications, 2024)
This study to examine the effect of profitability, mechanism good corporate governance (managerial ownership, independent commissioner, and audit committee), and firm size on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. This study uses secondary data. The analytical method used is quantitative method with purposive sampling technique and obtained 15 sample companies registered in the 2018-2022 period. The analysis in this study used SPSS 26 software. The results of this study are profitability, managerial ownership and independent commissioners has a positive and significant effect on firm.